Pengaruh Model Pembelajaran Problem Based Learning Terintegrasi STEAM terhadap Literasi Sains Siswa pada Mata Pelajaran IPA Biologi Kelas VII di SMP Negeri 37 Samarinda - Sari, Selvi Novita; Rambitan, Vandalita Maria Magdalena; Masitah, Masitah; Purwati, Sri; Makkadafi, Suparno Putera (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
The low science literacy of Indonesian students in the PISA study requires learning innovations that emphasize mastery of science concepts and their application in daily life. This study aims to determine the influence of the STEAM (Science, Technology, Engineering, Arts, and Mathematics) integrated Problem Based Learning (PBL) learning model on students' science literacy in the Biology Science subject grade VII at SMP Negeri 37 Samarinda. This study is a quasi experiment with a randomized pretest-posttest control group design. The research sample was obtained through a cluster random sampling technique consisting of class VII E as the experimental class and VII F as the control class. Data analysis includes normality test, homogeneity test, t-test, and N-Gain test. The results showed that the application of the STEAM integrated PBL model had a significant effect on improving students' science literacy as shown by the results of the t-test with a significance value of 0.000 (< 0.05). Thus, it can be concluded that the STEAM integrated PBL model is effective in improving students' science literacy. These findings indicate that the model could be an innovative and relevant alternative learning strategy to be implemented in secondary schools.